2010
DOI: 10.1071/wf08108
|View full text |Cite
|
Sign up to set email alerts
|

Integrating fuel treatment into ecosystem management: a proposed project planning process

Abstract: Concern over increased wildland fire threats on public lands throughout the western United States makes fuel reduction activities the primary driver of many management projects. This single-issue focus recalls a management planning process practiced frequently in recent decades – a least-harm approach where the primary objective is first addressed and then plans are modified to mitigate adverse effects to other resources. In contrast, we propose a multiple-criteria process for planning fuel-treatment projects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…odeling the impacts and effects of hazardous fuel reduction treatments is a pressing issue within the wildfire management community. Prospective evaluation of fuel treatments allows for comparison of alternative treatment strategies in terms of socioeconomic and ecological impacts and facilitates analysis of tradeoffs across land-management objectives (Stockmann et al 2010). Although much attention has been focused on assessing how fuel treatments affect expected loss to highly valued resources and assets (e.g., Ager et al 2007), some have also suggested benefits from fuel treatments in terms of avoided suppression costs (Snider et al 2006).…”
mentioning
confidence: 99%
“…odeling the impacts and effects of hazardous fuel reduction treatments is a pressing issue within the wildfire management community. Prospective evaluation of fuel treatments allows for comparison of alternative treatment strategies in terms of socioeconomic and ecological impacts and facilitates analysis of tradeoffs across land-management objectives (Stockmann et al 2010). Although much attention has been focused on assessing how fuel treatments affect expected loss to highly valued resources and assets (e.g., Ager et al 2007), some have also suggested benefits from fuel treatments in terms of avoided suppression costs (Snider et al 2006).…”
mentioning
confidence: 99%
“…Raw risk values inform risk mitigation planning and prioritization, but this information needs to be augmented with information on where treatments are likely to be effective, and to what degree risk can be reduced. The types of risk-based outputs from our framework can dovetail well with proposed decision analytic approaches for integrated, multi-attribute fuel management planning (Stockmann et al 2010;Hyde et al 2006;Ohlson et al 2006). This risk assessment framework that pairs fire modeling with fire effects analysis is scalable, meaning the same approaches can be employed from the project (e.g., Ager et al 2007) to the national scale (which we demonstrate here).…”
Section: Discussionmentioning
confidence: 90%
“…To be effective, decision-support tools for wildland fire management must account for the spatial nature of wildland fire phenomena (Blanchi et al 2002;Fairbrother and Turnley 2005;Stockmann et al 2010) Landscape condition and ecological functions result from sequences of multiple, recurrent spatially distributed processes (He 2008) which may exhibit non-linear responses as spatial extent increases (McKenzie et al 1996;Peters et al 2007). Spatial analysis of disturbance processes accounts for interactions within and beyond areas disturbed by wildfire and other processes.…”
Section: Spatial and Temporal Integrationmentioning
confidence: 99%
“…Multiple disturbance processes, e.g. those caused by fire, insects, disease, fuel reduction and forestry activities and invasive species, must be accounted for in order to integrate fire and fuels management into comprehensive ecosystem management (Stockmann et al 2010). Forecasting fire behaviour and fire effects for decision support in these systems which exhibit non-linear dynamics (Allen 2007;Davenport et al 1998) requires analysis of cross-scale temporal and spatial interactions if the 'surprises' of catastrophic events are to be minimised (Peters et al 2004).…”
Section: Spatial and Temporal Integrationmentioning
confidence: 99%